Fungsi Deiksis dalam Membangun Relasi Emosional Tokoh pada Film Pendek Seutas Kenangan: (Pendekatan Sosiopragmatik) - Mutiara Tantowi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study analyzes the function of deixis in building emotional relationships between characters in the short film "Seutas Kenangan" using a sociopragmatic approach. Besides being a medium for communication, language also functions as a medium for expressing distance, closeness, and social relationships that impact the emotional relationships that occur. Therefore, this study aims to examine how various types of deixis play a role in building emotional relationships between characters. The method used in this study is descriptive qualitative with data in the form of dialogues obtained through listening and note-taking techniques. This analysis was conducted by identifying the types of deixis, analyzing sociopragmatic aspects, and then interpreting the emotional relationships created. Based on the results of the study, there are deixis of person, time, place, social, and discourse that are related in representing emotional relationships. The emotional relationships found in this analysis include affection, longing, inner conflict, avoidance, and emotional stress due to prevailing social norms. The relationship between the function of deixis and the sociopragmatic approach shows that the function of deixis is not merely a referent indicator, but can also be a strategy for representing emotional relationships influenced by social and cultural conditions.